Pengaruh Penggunaan TikTok sebagai Media Pembelajaran Pendidikan Agama Islam Pada Era 4.0 - Nadita Fajarini; Habibah Amumpuni; Nur Ani Parida; Meilisa Sajdah (Jurnal Bintang Pendidikan Indonesia, 2024)
Currently the world has entered the era of the fourth industrial revolution. The advancement of modern technology will certainly affect developments in the world, both with regard to the issue of organizing education and from the ease of obtaining learning resources or knowledge. In this modern technological era, it is necessary to have truly unique and innovative learning, especially learning that can attract students' attention and interest in learning. Therefore, the objectives, structure and content of educational programs and learning media need to be changed so that learning becomes more interesting, accurate and attractive. This research was conducted at SMA PGRI 1 Kotabumi. The instrument used was a questionnaire regarding the effect of the use of TikTok on Islamic Religious Education subjects with the data analysis technique used in this study is to calculate the number of respondents' answers to each question. Students' Understanding of Islamic Religious Education Learning Activities using the TikTok Application according to PGRI 1 Kotabumi High School students understand Islamic Religious Education learning activities using the TikTok application, students can learn (review) learning material at any time and anywhere, and can increase student activeness and creativity.